Analisis Sistem Pembuatan Paspor pada Kantor Imigrasi Kelas II TPI Tanjung Balai Asahan - Amira Salsabila Afra Sihombing; Kusmilawaty Kusmilawaty (Jurnal Riset Akuntansi, 2024)
The aim of this research is to determine the passport making system at the TPI Tanjung Balai Asahan Class II Immigration Office. The approach used in this research is descriptive qualitative with data sources using primary data obtained through observation and interviews. The results of this research indicate that the passport making system at the TPI Tanjung Balai Class II Immigration office can be said to be not good. This can be seen from the many complaints from the public. Regarding that, not all people are allowed to register for a passport directly at the immigration office and it is only allowed for people aged 50 years and over. Another complaint made by the public to Customer Care is the difficulty of logging into the existing application system, which is only opened once a week, namely on Fridays at 18.00 WIB. Then another complaint is the long queue for processing online passport applications and the long passport processing process. Therefore, it can be recommended to increase the M-Passport registration schedule, provide information on using the system for making passports online so that problems do not occur, and improve the quality of passport making services so that the passport making process does not take a long time.